Integrating Network Pharmacology and Molecular Docking to Assess Rutin’s Pharmacological Properties - Govardhan R (International Journal of Molecular Biotechnological Research, 2023)
Objectives: In the present research, the network pharmacology process was applied to determine the underlying mechanism of the pharmacological properties of Rutin. Network pharmacology was utilized to reveal the interactions between medications and the targets of illnesses, and it is capable of completely articulating the complexity between diseases and medications. The identification of diverse drug-target interactions using network pharmacology may be utilized to discover novel medications for difficult conditions like Parkinson’s and Alzheimer’s diseases. Rutin’s considerable antioxidant capabilities have led to a broad range of pharmaceutical uses. Methods: In this research, the binding affinity of Rutin corresponding to the targeted proteins was analyzed (TNF, ALOX5, PTGS2, IL2 and TERT). Pathway evaluation for these targets showed a nitrogen metabolism pathway. An online tool called PyRx was used to perform molecular docking. The study was done virtually using input and structure of protein and phytocompounds from UniProtKB and PubChem. With the help of BIOVIA Discovery Studio software, the protein structure was analyzed. ADMET screening was used to evaluate the Rutin’s pharmacological properties. Results: The results from this research showed that the proteins ALOX5 and PTGS2 had the best binding affinity to Rutin in performing molecular docking. Conclusion: According to the results of molecular docking, these target proteins have appropriate pharmacological effects, which offers a theoretical foundation and a hint for the investigation of the pharmacological mechanism of Rutin.
Keywords: Parkinson’s and Alzheimer’s disorders; molecular docking; network pharmacology; nitrogen metabolism pathway